A fractionally integrated ECOGARCH process - Stephan Haug; Claudia Czado (Ludwig-Maximilians-Universität München, Sonderforschungsbereich 386 - Statistische Analyse diskreter Strukturen, 2006)
In this paper we introduce a fractionally integrated exponential continuous time GARCH(p,d,q) process. It is defined in such a way it is a continuous time extension of the discrete time FIEGARCH(p,d,q) process. We investigate stationarity and moment properties of the new model. It is also shown that the long memory effect introduced in the log-volality propagates to the volality process.
urn:nbn:de:bvb:19-epub-1852-7
Keywords: 519; fractionally integrated exponential continuous time GARCH process; long memory FIEGARCH; ECUGARCH; Lévy process; stationarity; stochastic volatility